AB0521 Safety, pharmacokinetics, and pharmacodynamics of single doses of a bispecific icosl and baff inhibitor, amg 570, in healthy subjects. (12th June 2018) - Cheng, L.E.; Kankam, M.; Siebers, N.; Stoltz, R.; Abuqayyas, L.; Ertik, B.; Sullivan, B.A.; Zhou, L.; Mitragotri, D.; Parnes, J.R.
Abstract : Background: Autoimmune diseases, including systemic lupus erythematosus (SLE), are associated with dysregulation in both T cell and B cell responses. Targeting the activity of both cell types simultaneously holds promise as a treatment for autoimmune disease. AMG 570 is a bispecific molecule targeting both T cell and B cell activity through neutralisation of the inducible costimulator ligand (ICOSL) and the B cell activating factor (BAFF). Objectives: To investigate the safety, tolerability, pharmacokinetics, and pharmacodynamics of AMG 570 in healthy subjects after single subcutaneous doses. Methods: This ongoing, double-blind, randomised, placebo-controlled trial has enrolled healthy subjects (age ≥18 years) into escalating single-dose cohorts. Eight participants were enrolled into each cohort and were randomised 3:1 to receive either AMG 570 or placebo across six cohorts of increased dose level. The primary endpoint of the study was treatment-emergent adverse events (AEs). Secondary endpoints included pharmacokinetics and pharmacodynamics (eg, receptor occupancy of ICOSL, changes in B cell subpopulations, and serum immunoglobulin levels). Results: As of an ad hoc interim analysis on October 5, 2017, 48 participants were enrolled and received one dose of investigational product (either AMG 570 or placebo). 73 AEs were reported; all were mild (n=56) to moderate (n=14) in severity (3 injury AEs had no grade reported). Upper respiratory tract infection and injection site erythema were the most commonly reported AEs. No drug-related serious adverse events were reported. No severe, life-threatening, or fatal AEs were reported. AMG 570 demonstrated nonlinear pharmacokinetics consistent with cell surface target (ICOSL) interaction. In the highest dose tested, AMG 570 achieved greater than 90% mean ICOSL receptor occupancy on circulating B cells 8 days after dosing, and high levels (>85% mean ICOSL receptor occupancy) were observed 29 days after dosing. AMG 570 led to a reduction in circulating naïve B cells and an increase in circulating memory B cells. No apparent changes were observed in serum IgM or IgG. Conclusions: Overall, AMG 570 was safe and well tolerated by healthy subjects. AMG 570 demonstrated pharmacodynamic activity consistent with ICOSL and BAFF neutralisation. Disclosure of Interest: L. Cheng Shareholder of: Amgen Inc., Employee of: Amgen Inc., M. Kankam: None declared, N. Siebers: None declared, R. Stoltz: None declared, L. Abuqayyas Shareholder of: Amgen Inc., Employee of: Amgen Inc., B. Ertik Shareholder of: Amgen Inc., Employee of: Amgen Inc., B. Sullivan Shareholder of: Amgen Inc., Employee of: Amgen Inc., L. Zhou Shareholder of: Amgen Inc., Employee of: Amgen Inc., D. Mitragotri Shareholder of: Amgen Inc., Employee of: Amgen Inc., J. Parnes Shareholder of: Amgen Inc., Employee of: Amgen Inc.